2021
DOI: 10.3389/fpsyg.2021.701627
|View full text |Cite
|
Sign up to set email alerts
|

Can We Commit Future Managers to Honesty?

Abstract: In a competitive business environment, dishonesty can pay. Self-interested executives and managers can have incentive to shade the truth for personal gain. In response, the business community has considered how to commit these executives and managers to a higher ethical standard. The MBA Oath and the Dutch Bankers Oath are examples of such a commitment device. The question we test herein is whether the oath can be used as an effective form of ethics management for future executives/managers—who for our experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Nevertheless, our insights can be important for designing interventions in such applied settings. Similarly, previous studies have shown that honesty oaths can be effective across a range of outcome behaviors including dishonesty in economic game tasks, [58][59][60][61] preference elicitation, 62,63 tax compliance, 22 and cheating in online exams. 64 Our study replicates this general finding and provides an overview of boundary conditions and effective formulations.…”
Section: Limitations and Constraints On Generalizabilitymentioning
confidence: 65%
“…Nevertheless, our insights can be important for designing interventions in such applied settings. Similarly, previous studies have shown that honesty oaths can be effective across a range of outcome behaviors including dishonesty in economic game tasks, [58][59][60][61] preference elicitation, 62,63 tax compliance, 22 and cheating in online exams. 64 Our study replicates this general finding and provides an overview of boundary conditions and effective formulations.…”
Section: Limitations and Constraints On Generalizabilitymentioning
confidence: 65%
“…Despite the merits of remote settings, many workers are left unmonitored, leading to costly agency problems involving misreporting —the worker executes the task but lies about quality, productivity, performance, or outcome—and shirking —the worker minimizes effort and fails to complete the task at all, yet seeks compensation. Lying in strategic and nonstrategic settings is well documented in the lab and in online experiments (e.g., Beck et al, 2018 ; Erat & Gneezy, 2012 ; Fischbacher & Follmi-Heusi, 2013 ; Gneezy et al, 2018 ; Jacquemet et al, 2018 , 2019 , 2021b ; Rosaz & Villeval, 2012 ; Tergiman & Villeval, 2021 ) and is typically viewed as deviant behavior involving a trade-off between psychological costs and unethical benefits (e.g., Abeler et al, 2014 ; Becker, 1968 ; Brink et al, 2019 ). Because plausible lies are, by their nature, the most difficult to detect and extremely common, they are often the costliest.…”
Section: Motivationmentioning
confidence: 99%